Problem Based Learning in Teaching Speaking at Senior High School - Kencanawati, Dewi; Aina, Rida Sya’wanatul (English Education:Journal of English Teaching and Research, 2016)
It is believed that speaking is difficult subject because it is not only learn about pronouncing the words. The writer uses quantitative approach in this research because to know the effect of problem based learning to the students’ speaking ability at the eleventh grade students of XII science class of SMAN 4 Kediri that consists of 25 students. The spoken tests, in the form of pre and post test were used to collect the data. The holistical rating on speaking rubric form was used to score the students’ speaking ability before and after the treatments of teaching speaking using problem based learning (PBL)The research result severals that students’ skill in speaking is still considered low. The pre-test result indicated that, the totaly score of pre-test is 1306,75 and the mean of pre-test is 52,27. The highest score is 66, 67 and the lowest score of pre-test is 25. It can be concluded that mostly the students had a difficulty in speaking English. Their score is unsatisfying because the English standard score of the school is 70. By being given series of trestments with PBL students’ speaking skill improved. The totaly of post-test is 1544,75 and the mean of post-test is 61,79. The post-test result showed that the highest score is 75. Unfortunately, the lowest score of pre-test is 30. It can be concluded that there is an increasing score of students’ speaking ability after post-test is conducted. It is clear to be seen from the changing of students’ score. There are many students get better score than before The result of this research shows that t-score is 12, 67 at the degree of freedom 24 which was higher than the value of t-table was 1,711 at the level of significance 5% and value of t-table is 2,492 at the level of significance 1%. It means that t-score was very significant.Suggestion are purposed for English teacher who should give their students stimuli, to analyze the problem and try to find solution to the problem as well. Then, for the other researcher, the researcher hopes that other researchers could improve the content of this study by adding more explanation, example, and references.